Educação não-formal e divulgação de astronomia no Brasil : atores e dinâmica da área na perspectiva da Complexidade - Marques, Joana Brás Varanda (2017)
This research focuses on non-formal education and dissemination of astronomy in the Brazilian context. In previous works, we have already investigated this theme and obtained, through a Delphi study, an overview of the main problems of the area and some of the possible solutions for them, according to the opinion of a representative set of specialists. The present research has as it main objective the construction of a portrait of the non-formal education of astronomy in Brazil having as theoretical and methodological basis the theory of complexity. This foundation allows us to have a multidimensional view of this theme, to perceive its structures, but also its relations, and to identify patterns, contradictions and complementarities. We used, as data sources, the responses given to the previous Delphi study by the 34 specialists who participated in this study until the end. Through content analysis, we developed two categorizations of the experts' opinions on systemic networks - one thematic and the other complex. The thematic systemic network allows us to describe the area in terms of the following categories: disseminators, public, offer, research, working conditions, financing and relation with formal education. The complex systemic network allows us to look at the area as a system and to analyze the structures, functions, flows and processes involved, as well as different temporal and scalar levels in which the system evolves. In addition to the description and understanding of the area that can be obtained using these categorizations, we also sought, through statistical techniques of cluster analysis, to investigate the existence of patterns and response profiles that allow for a clearer understanding of the different dynamics and realities that make up this heterogeneous area. This analysis was based on the results of the systemic networks together with the characterization data of the specialists (age, years of experience, area of action, etc.). We contend that this more detailed study is of great interest to the area of non-formal education and dissemination of Astronomy in Brazil, because it clarifies the area based on a deep self- reflection. This study presents a contribution to the area of non-formal education and dissemination of astronomy in Brazil, because it has as result the clarification of a profound and unprecedented reflection that the area has done on itself, through its expert members.